The effectiveness of IMB-model based diabetes self-management education with type 2 diabetes patients in Jordan: clinical trial protocol - Albelbisi, Zaki; Windle, Richard; Blake, Holly (2015)
Abstract for AADE Annual Meeting conference: Background: According to the World Health Organization in 2014, 9% of adults over 18 years old are diagnosed with diabetes and more than 1.5 million deaths occur directly by diabetes in low and middle-income countries. Ajlouni et al (2008) estimated that approximately one million people in Jordan have been diagnosed with type 2 diabetes; a figure that is increasing. To prevent diabetes microvascular and macro vascular complications, increased efforts and attention need to be directed towards improving glycaemic levels and improving metabolic outcomes through appropriate glycaemic management and this may be best achieved through educating patients in self-management of diabetes. Barriers in diabetes self-management behaviours were found to be consistent with Information-Motivation-Behavioural skills (IMB) Model of behavioural change. 2- Aim: to examine the effects of IMB Model-based Diabetes Self-Management Educational (DSME) intervention on three self-management activities: patients’ eating habits, physical activity and medications management, in patients who attend the (NCDEG). 3- Research protocol and methods: A two group trial with randomised allocation of 230 participants on 1:1 average for both groups. Intervention group will receive the educational intervention. Control group will receive usual clinical care and referral to diabetes educational consultation if required. This study will implement an individualised DSME program based on Information-Motivation-Behavioural (IMB) skills theory. IMB behavioural change theory assumption proposes that health-related behaviour information, motivation and behavioural skills are primary determinants of promoting health behaviour. Researcher will use a validated DSME toolkit and will be delivered using motivational interviewing techniques through two face-to-face sessions (one at the beginning and one at the end) and several phone calls intervention for each participant during a period of 3 months from participation. Both groups will be assessed at 2 follow-up times (after 3 months and 6 months) for self-management knowledge, motivation, behavioural skills, diabetes level (HbA1c), blood pressure and weight from baseline assessment (time of participation). After delivering the intervention to participants in the intervention group immediately (after 3 month), a purposive sampling approach will be used to choose 15 participants for an interview to ask them to evaluate the process of implementing of the educational intervention. 4- Implications for practice/research: This clinical trial will make a knowledge contribution about conceptualizing behavioural change techniques as well as individually and culturally tailored needs, within self-management educational intervention for patients with DM. Moreover, this trial designed on three main operations: assessing, implementation and evaluation. Competently, each operation is constructed on IMB model elements, which will provide a comprehensive understanding of how Jordanian patients’ Knowledge, Motivation, Behavioural skills and metabolic outcomes changes overtime, in tandem with performing self-management behaviours over three main points of time, pre-and-post intervention and post follow up.